Early postoperative pain after laparoscopic donor nephrectomy predicts 30-day postoperative infectious complications: a pooled analysis of randomized controlled trials. Issue 7 (July 2020) - Albers, Kim I.; van Helden, Esmee V.; Dahan, Albert; Martini, Chris H.; Bruintjes, Moira H.D.; Scheffer, Gert-Jan; Steegers, Monique A.H.; Keijzer, Christiaan; Warlé, Michiel C.
Abstract : Abstract: Our research group recently published a positive association between early postoperative pain and 30-day postoperative complications in a broad surgical population. To investigate whether heterogeneity of the population and surgical procedures influenced these results, we explored this association in a homogenous surgical population. A secondary analysis of the LEOPARD-2 (clinicaltrials.gov NCT02146417) and RELAX-1 study (NCT02838134) in laparoscopic donor nephrectomy patients (n = 160) was performed. Pain scores on the postanesthesia care unit and postoperative day (POD) 1 and 2 were compared between patients with infectious, noninfectious, and no complications 30 days after surgery. Patients who developed infectious complications had significantly higher pain scores on POD1 and 2 (6.7 ± 2.1 and 6.4 ± 2.8) than patients without complications (4.9 ± 2.2 and 4.1 ± 1.9), respectively ( P = 0.006 and P = 0.000). Unacceptable pain (numeric rating scale [NRS] ≥ 6) on POD1 was reported by 72% of patients who developed infectious complications, compared to 38% with noninfectious complications and 30% without complications ( P = 0.018). This difference was still present on POD2 at 67% with infectious complications, 21% with noninfectious, and 40% without complications ( P = 0.000). Multiple regression analysis identified unacceptable pain (numeric rating scale ≥6) on POD2 as a significant predictor for 30-day infectious complications (odds ratio 6.09, P = 0.001). Results confirm the association between early postoperative pain and 30-day infectious complications in a separate, homogenous surgical population. Further clinical trials should focus on finetuning of postoperative analgesia to elucidate the effects on the endocrine and immune response, preserve immune homeostasis, and prevent postoperative infectious complications. Abstract : A secondary analysis of prospective clinical trials in living kidney donors demonstrates the association between postoperative pain and infectious complications in a homogenous surgical population.